2018
DOI: 10.1093/rheumatology/kex465
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and cerebrovascular comorbidities of juvenile dermatomyositis in US children: an analysis of the National Inpatient Sample

Abstract: There are significantly higher odds of cardiovascular and cerebrovascular comorbidities among inpatients with JDM, with adolescents, girls and racial/ethnic minorities being at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…Cardiovascular manifestations of juvenile dermatomyositis (JDM), the most common idiopathic inflammatory myopathy of childhood, include acquired structural abnormalities, ventricular dysfunction, arrhythmias, myocarditis, and hypertension [11][12][13][14][15][16][17], with myocardial infarction acting as a rare cause of death [11,13,18,19]. JDM shares the same atherogenic risk factors and vasculopathic features as those of other rheumatologic illnesses, with the added component of lipodystrophy and its related metabolic derangements [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular manifestations of juvenile dermatomyositis (JDM), the most common idiopathic inflammatory myopathy of childhood, include acquired structural abnormalities, ventricular dysfunction, arrhythmias, myocarditis, and hypertension [11][12][13][14][15][16][17], with myocardial infarction acting as a rare cause of death [11,13,18,19]. JDM shares the same atherogenic risk factors and vasculopathic features as those of other rheumatologic illnesses, with the added component of lipodystrophy and its related metabolic derangements [15,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Other manifestations include myocardial infarction, myocarditis, cardiomyopathies, valvular heart disease, pericarditis, pericardial effusion, pulmonary oedema, arrhythmias and conduction block, pulmonary arterial hypertension and venous thromboembolism 23 24. Not only the risk related specifically to the DM (such as myocardial inflammation, endomyocardial fibrosis, small vessel vasculitis, accelerated atherosclerosis),23 but also the traditional risk factors of heart diseases were more prevalent among them 25. As risk of cardiac complications are more common than general population26 27 and the most common cause of death among DM patients,23 they should be evaluated for cardiac comorbidity at the time of diagnosis of myositis 28.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a small pilot study compared carotid intima-media thickness (CIMT) and flow-mediated dilatation (FMD) as surrogate markers of atherosclerosis in 8 adults with a history of JDM and revealed increased CIMT in JDM patients compared to 8 healthy controls despite the young age ( 37 ). Moreover, recently a large retrospective study demonstrated that JDM was associated with higher odds of cardiovascular and cerebrovascular disease in adolescents, including atherosclerosis, transient ischaemic attacks and cerebral infarction ( 43 ). It is thus possible that the combination of chronic endothelial injury caused by persistent small vessel vasculitis, chronic systemic inflammation, long-term corticosteroid use, sedentary lifestyle, and conventional cardiovascular risk factors predispose patients with JDM to early atherosclerosis.…”
Section: Pathophysiologymentioning
confidence: 99%